Pola Komunikasi Orang Tua Terhadap Anak dalam Membiasakan Shalat Berjamaah di Masjid Al-Hasan Desa Simpang Padang Kecamatan Bathin Solapan Kabupaten Bengkalis - Silvia Zahrani; Penmardianto Penmardianto (KOLONI, 2024)
This research was motivated by a phenomenon where at the research location there were many children aged 6-12 years who regularly performed congregational prayers at the mosque. Even though at that age children will be busy with their own world according to the child's psychological development. Parents who succeed in getting their children to pray together at the mosque certainly have their own communication patterns. The method used in this research is qualitative with a descriptive approach using observation, interview and documentation stages and using data analysis techniques. The results of the research obtained by the author state that the communication patterns used by parents with children in getting used to congregational prayers at the Al-Hasan Mosque, Simpang Padang Village, Bathin Solapan District are very diverse. There are three communication patterns, namely the Permissive communication pattern, where children have the freedom to act according to their wishes, parents always give in and pamper their children. Second, the Authoritarian communication pattern, namely parents strictly control their children, are harsh and like to punish children. Third, the Democratic (Authoritative) communication pattern, namely there is agreement between parents and children, parents respect the child's opinion.